2005
DOI: 10.1128/jvi.79.8.5059-5068.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Murine Gammaherpesvirus 68 ORF27 Gene Product Contributes to Intercellular Viral Spread

Abstract: Herpesviruses remain predominantly cell associated within their hosts, implying that they spread between cells by a mechanism distinct from free virion release. We previously identified the efficient release of murine gammaherpesvirus 68 (MHV-68) virions as a function of the viral gp150 protein. Here we show that the MHV-68 ORF27 gene product, gp48, contributes to the direct spread of viruses from lytically infected to uninfected cells. Monoclonal antibodies to gp48 identified it on infected cell surfaces and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 35 publications
3
56
0
Order By: Relevance
“…However, in contrast with other rhadinoviruses, BoHV-4 does not encode any ORF4 or ORF74 homologues, and only four other potential envelope glycoproteins were predicted in the BoHV-4 genome: ORF27, ORF53, ORF58, and Bo9. The proteins encoded by ORF27 and ORF58 are involved in intercellular viral spread in MuHV-4 (35,36). One hypothesis could therefore be that different virions are produced following the major way of dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast with other rhadinoviruses, BoHV-4 does not encode any ORF4 or ORF74 homologues, and only four other potential envelope glycoproteins were predicted in the BoHV-4 genome: ORF27, ORF53, ORF58, and Bo9. The proteins encoded by ORF27 and ORF58 are involved in intercellular viral spread in MuHV-4 (35,36). One hypothesis could therefore be that different virions are produced following the major way of dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that bdlf2 is a late gene in the EBV lytic cycle in epithelial cells. May et al (2005b) recently showed that ORF27, a distantly related BDLF2 homologue from murine herpesvirus 68 (MHV-68) is required for cell-to-cell spreading. However, the same authors revealed that ORF27 interacts with ORF58, the BMRF2 homologue, and this interaction influences their subcellular distribution (May et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…May et al (2005b) recently showed that ORF27, a distantly related BDLF2 homologue from murine herpesvirus 68 (MHV-68) is required for cell-to-cell spreading. However, the same authors revealed that ORF27 interacts with ORF58, the BMRF2 homologue, and this interaction influences their subcellular distribution (May et al, 2005b). It appears that the expression of ORF58 is sufficient to induce the export of ORF27 from the endoplasmic reticulum (ER) and transport of the noncovalent ORF58/ORF27 complex to the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Ab has effector functions other than neutralization. For example, it is likely that Ab plays a role in controlling viral spread and viral reactivation, as gp150 and gp48 have been shown to promote virion release and intercellular viral spread (57)(58)(59). Since both humoral and cellular immunity have been shown to be involved in controlling distinct stages of ␥-herpesvirus infection, and the importance of neutralizing Abs for viruses that spread mainly by cell-cell contact is unclear, we cannot conclude that the absence of neutralizing Abs following i.p.…”
Section: Discussionmentioning
confidence: 99%